Experimental in-situ testing of typical masonry constructions of Faial Island - Azores - António Arêde (2008)
The present paper focuses on an in-situ testing campaign recently developed in the Faial island, Azores, Portugal, aiming at the assessment of the out-of-plane behaviour of traditional stone masonry walls. This experimental activity, carried out by the Laboratory for Earthquake and Structural Engineering (LESE, FEUP, Porto), started developing some years after the Faial/Pico earthquake on July 9th 1998, in order to provide adequate characterization of the structural response under loading types likely to induce out-of-plane motion of walls as the case of the seismic action. A general description is included concerning cyclic tests carried out to date, complemented with the presentation and discussion of the most important results. Numerical predictions of strength based on simple models are also provided for one tested wall indicating good agreement with experimental findings. This in-situ programme involved a second stage for structural strengthening according to schemes similar to some of those adopted during the reconstructions process in Faial Island. Further tests were then performed in order to assess the seismic capacity improvement of the strengthened structures, leading to interesting and promising results concerning both strength and energy dissipation enhancement. The paper also highlights that such type of tests is viable and constitute an excellent means of assessing structural parameters for masonry walls as they exist in reality, in order to feed suitable non-linear behaviour models for structural analysis.